Public School Heads’ Leadership Style and Best Practices in the Depart-ment of Education in Bulacan, Philippines - Estacio, Madonna R.; Estacio, Dennis L. (Future Science / FSH-PH Publications, 2022)
This study aims to determine the leadership style and the best practices of the school heads in the department of education in Bulacan. In the Philippines, there shall be a school head for all public elementary and secondary schools or as cluster thereof, pursuant to Section 6.1, Rule VI of the Implementing Rules and Regulations of the Republic Acts No. 9155 (Governance of Basic Education Act of 2001). A school head is a person responsible for the administrative and instructional supervision of the school or cluster if schools. As such, a school head is expected to possess the following leadership: educational leadership, people leadership and strategic leadership. The study will use the Research Design, Qualitative, Quantitative and Mixed Methods Approaches (Creswell, 2014), extensive documentary analysis was employed. Every school heads function as leaders resulted to improved learners’ profound academic performance, brought by a strong leadership formulated an achievable vision, mission in accomplishing the goal. Best practices were clearly demonstrated as the indicators of better and improving school learning environment.